New Green, Recyclable Magnetic Nanoparticles Supported Amino Acids as Simple Heterogeneous Catalysts for Knoevenagel Condensation - Girija, D.; Bhojya Naik, H.S.; Vinay Kumar, B.; Sudhamani, C.N.; N. Harish, K. (Letters in Organic Chemistry, 2013)
Coumarin derivatives were synthesized using magnetically recoverable iron oxide nanoparticles supported amino acids as heterogeneous catalysts via one-pot multi component reaction using MW irradiation. Easy recovery of the catalyst using an external magnet, efficient recycling, and reusable without significant loss of their catalytic efficiency makes the protocol greener and sustainable.
Keywords: Fe3O4-DA-Phe